The Effect of Corporate Governance On Financial Performance With CSR as A Moderating Variable - Musdalifa, Musdalifa; Afrizal, Afrizal; Putra , Wirmie Eka; Wijaya, Riko (International Journal of Entrepreneurship and Business Management, 2024)
This study aims to provide new evidence on the comparison of the implementation of Corporate governance on the financial performance of Indonesian and Malaysian Islamic banking from 2016 to 2020. The authors uses multiple regression analysis with samples of Indonesian and Malaysian Islamic banks from 2016 to 2020. The data used are obtained from the financial statements of Indonesian and Malaysian Islamic banks from 2016 to 2020. Financial performance is measured by profitability ratios using return on assets (ROA). CSR from the test results were not able to moderate the financial performance of Indonesian and Malaysian Islamic companies from 2016 to 2020. This study is a comparative study of the effect of the implementation of Corporate governance on the financial performance of Islamic banking companies in Indonesia and Malaysia with CSR as the moderating variable.